Interprofessional education with simulations in primary care - Klemenc-Ketiš, Zalika (Zdravstveno varstvo, 2024)
The introduction of interprofessional primary care (IPC) as a model of collaborative patient care is increasingly vital in the context of complex healthcare systems and the growing needs of patients. Its benefits include improved patient outcomes, enhanced efficiency, and reduced costs. However, the successful implementation of IPC faces challenges due to the differences in training and backgrounds among healthcare professionals, emphasising the importance of effective teamwork and collaborative education. Educational approaches utilising simulations have gained prominence, particularly in addressing the challenges of interprofessional primary care. Notably, simulations facilitate team learning, enhancing team management and confidence, which ultimately leads to improved performance in real-life scenarios. They also contribute to patient safety by providing comprehensive training and creating a safe environment for professionals to practice and refine their skills without risking real patient harm. Moreover, simulations promote psychological safety, allowing healthcare workers to manage stress effectively and prepare for critical situations. Ethical considerations are met through simulation-based education, ensuring patient confidentiality, and creating a standardised and just learning environment for all students. Simulations contribute to promoting equity in medical education by providing equal access to high-quality training opportunities for all healthcare professionals. In conclusion, successful IPC implementation requires a comprehensive approach that includes interprofessional education and the integration of simulations as an essential component of the curriculum at all levels of healthcare education. This approach fosters effective communication, teamwork, and confidence among primary care teams, ultimately leading to improved patient care and outcomes.
Keywords: education; interprofessional primary care; izobraževanje; medpoklicno primarno zdravstveno varstvo; patient safety; simulacije; simulations; teamwork; timsko delo; varnost pacientov